Revisiting Agrarian Reform in Brazil, 1985–2016. Issue 1 (March 2018) - Robles, Wilder
This article examines Brazil's experience in agrarian reform from 1985 to 2016. After more than three decades of agrarian reform, Brazil remains a country with highly skewed landownership. Peasant-led agrarian reform efforts have had limited impact in changing this situation. Agrarian reform remains an unfulfilled political promise, and this situation continues to create tensions and conflicts in the countryside. The main reason for the persistence of skewed land concentration is the State's support of agribusiness. Successive post-1985 democratic governments have encouraged the opening of new agricultural frontiers by providing generous economic incentives. Land redistribution has been offset by further land possession; that is, the expansion of small-scale agricultural farming has been counterbalanced by the expansion of large-scale, capital intensive agriculture. Agribusiness has not only undermined agrarian reform efforts but has also generated a growing dependency on a socially and environmentally destructive monoculture agricultural economy. Moreover, Brazil's current political and economic crisis has further undermined the struggle for agrarian reform.